Students’ and Teachers’ Perceptions of Using Memes in ESL Classrooms - Youssef, Fadwa (AUC Knowledge Fountain, 2023)
Using humor in the language classroom has proven to be an effective pedagogical teaching tool that builds rapport between students and teachers. It also reduces anxiety and affective filter as well as increases students’ performance and willingness to communicate in class using their L2 (Azizinezhad & Hashemi, 2011; Banks, 2014; Soares, 2015). Previous studies used humor broadly starting from humorous comments in class to funny TV shows, movies, or songs. Some studies went further using funny memes in class and fewer studies went all the way making students create memes as part of their class requirements (Purnama, 2017). Results of previous studies demonstrated the efficiency of humor in increasing students’ social competence and acquiring their L2 culture (Navera et al., 2019). Using the Immediacy framework, this study investigates the Egyptian university ESL teachers and students’ perceptions of using memes in class. It also looks into the variables affecting these perceptions like proficiency and age. Results shed light on the positive and negative impacts students and teachers think memes have in class as well as the contexts and frequency in which they used memes in ESL classroom.